A Narrative of the Troubles in the Second Church in Windsor, 1735-1741 [part II] - Mullen, Lincoln A. (Jonathan Edwards studies, 2013)
In 1740-41, the laypeople of the Congregational church in East Windsor drew up a lengthy document, "A Narrative of the Troubles in the Second Church in Windsor, 1735-1741." The narrative describes a six-year conflict within the church, and embedded within it are letters, church records, and the proceedings of church councils relating to the affair. The dispute was between the Rev. Timothy Edwards and his supporters, on the one one hand, and a party of the laity headed by the future Connecticut governor Roger Wolcott, on the other. At stake were two issues: first, what powers belonged to the minister and to the membership in cases of church discipline, and by what procedures those powers should be exercised; second, whether one Joseph Diggins could be barred from owning the covenant, and thus whether his children could be barred from baptism.